Experimental investigation on energy absorption of auxetic structures - Najafi, Milad; Ahmadi, Hamed; Liaghat, Gholamhossein (Materials today : proceedings, 2021)
The human being has always been looking for optimal use of his surrounding materials and over the years, has managed to invent various structures with special properties. Lattice structures are widely used in various applications due to their lower weight and desirable compressive strength. An example of these structures is the honeycomb that is very popular and many studies have been done about it. A new type of lattice structures is auxetic structure that has negative Poisson’s ratio due to its geometry. This characteristic has caused auxetic structures to have unique properties such as high shear strength, indentation resistance and energy absorption. Investigation of energy absorption of auxetic structures is a subject that has not been studied in researches. In this study, the ability of some auxetic structure for absorbing energy is investigated at quasi-static and low velocity impact transverse loading. Specimens with three types of geometries (re-entrant, arrowhead and anti-tetra chiral) are fabricated using additive manufacturing method (3D printing). Discussion about energy absorption and failure mechanisms of all three structures were carried out and compared in both types of loading.